Developing phosphonic acid bearing polyelectrolytes for their biocidal activity on surfaces, thermal properties, nanofiber and nano particle formation - Suer, N. Ceren; Yapaoz, Melda Altikatoglu; Arasoglu, Tulin; Gallei, Markus; Eren, Tarik (ELSEVIER, 2021)
Bacteria infection is a growing problem all over the world. Within this contribution, phosphonium-phosphonic acid or hexyl pyridinium-phosphonic acid bearing copolymer series derived via ring opening metathesis polymerization (ROMP) method are synthesized to investigate their biocidal activity on the glass surface. The presence of phosphonic acid moieties enhanced the coating capability on the iron oxide nanoparticles and the thermal properties of the copolymers. Biocidal activities of the polymers and iron oxide bearing polymers were tested against E.coli and S.aureus. Polymers possessing higher activity was then blended with commercial polyacrylonitrile for the nanofiber formation via electrospinning methods.
Keywords: Electrospinning; Antimicrobial Polymers; Polyacrylonitrile; ROMP; Iron oxide nanoparticles; IRON-OXIDE NANOPARTICLES; OPENING METATHESIS POLYMERIZATION; MAGNETITE NANOPARTICLES; ELECTROSPUN NANOFIBERS; BLOCK-COPOLYMERS; ANTIBACTERIAL; MEMBRANES; FUNCTIONALIZATION; STABILIZATION; Materials Science